Quelques documents sur la corporation des Mozabites d’Alger dans les premiers temps de la conquête (1830-1838) - Lespès, René (Revue Africaine, 1925)
A critical study with reference to a letter of Mīzābīs in Algiers to the commander of the French occupying forces intended to keep the priviliges they had acquired under the Turks.
Keywords: Emigration – Mzab – Algérie